ANALISIS OPERASIONAL PEMBANGKIT LISTRIK TENAGA SURYA ATAP PADA GEREJA MASEHI INJILI DI TIMOR KAISAREA KOLHUA KUPANG - Nahas, Reflianus H.; Likadja, Frans J.; Galla, Wellem F. (Jurnal Media Elektro, 2025)
On-Grid Rooftop Solar Power Plant (PLTS) is interconnected with the PLN network and has a capacity of 25 kWp at GMIT Kaisarea BTN-Kolhua Kupang, which is expected to reduce significant operational costs. Therefore, this study aims to determine the performance ratio and the amount of energy potential contained in the Rooftop Solar Power Plant (PLTS) at GMIT Kaisarea BTN-Kolhua Kupang in order to optimize the use of renewable energy and reduce electricity operational costs. The research method used is a descriptive method and direct measurement on the inverter, MDP, and LVMDP to measure current and voltage to obtain the output power of the PLTS, PLN, and load. The results of the study indicate that the Rooftop Solar Power Plant (PLTS) system at GMIT Kaisarea BTN-Kolhua Kupang performed well, as evidenced by the efficiency of the Rooftop Solar Power Plant (PLTS), which obtained a maximum value of 85.60% on Monday of 85.60%. The measurement results show that there are savings in power and bills at GMIT Kaisarea BTN-Kolhua Kupang, with savings for 7 consecutive days of (Saturday 19.58 kWh, Sunday 76.84 kWh, Monday 9.45 kWh, Tuesday 24.05 kWh, Wednesday 22.46 kWh, Thursday 23.30 kWh, Friday 32.92 kWh).